On Kolm's Theory of Macrojustice A Pluridisciplinary Forum of Exchange - Gamel, Claude; Lubrano, Michel (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
The "Theory of Macrojustice, introduced by S.-C. Kolm, is a stimulating contribution to the debate on the macroeconomic income distribution. The solution called Equal Labour Income Equalisation (ELIE) is the result of a three stages construction: collective agreement on the scheme of labour income redistribution, collective agreement on the degree of equalisation to be chosen in that framework, individual freedom to exploit his--her personal productive capicities (the source of labour income and the sole basis for taxation). This book is organised as a discussion around four complementary themes: philosophical aspects of macrojustice, economic analysis of macrojustice, combination of ELIE with other targeted tranfers, econometric evaluations of ELIE.
Why Should We Debate the Theory of Macrojustice?- THE MACROJUSTIC OF SERGE-CHRISTOPHE KOLM: General Presentation -- Economic Macrojustice: Fair Optimum Income Distribution, Taxation and Transfers -- PHILOSOPHICAL ASPECTS OF MACROJUSTICE: ELIE and the Emotions Related to Social Recognition -- Basic Income and ELIE Transfers: Argument for Comatibility Despite Divergence -- ECONOMIC ANALYSIS OF MACROJUSTICE: An Axiomatic Study of the Equal-Labour-Income Equalisation Allocation Rule -- An Exploration of Incentive-Compatible ELIE -- COMBINATIONS OF ELIE WITH OTHER TARGETED TRANSFERS: Is ELIE a wasteful minimum income scheme?- ELIE-minating Poverty? Limits of the Mechanism and Potential Improvements -- ECONOMETRIC EVALUATIONS OF ELIE: The Redistributive Aspects of ELIE: A Simulation Approach -- The Tradeoff Between Growth and Redistribution: ELIE in an Overlapping Generations Model -- SELECTIVE COMMENTS BY SERGE-CHRISTOPHE KOLM: Macrojustice in Normative Economics and Social Ethics.
Electronic reproduction.
Keywords: Distributive justice; Income distribution; Economics -- Moral and ethical aspects; Wealth; Poverty; Electronic books